Who Provides Gastrointestinal Endoscopy in Canada?. (2007) - Hilsden, Robert J; Tepper, Joshua; Moayyedi, Paul; Rabeneck, Linda
Abstract : PURPOSE: To determine who provides gastrointestinal endoscopy in Canada and to understand provincial and regional differences in endoscopy providers. METHODS: Aggregate physician sociodemographic and activity data for 2002 were obtained from the Canadian Institute of Health Information's National Physician Database. Physicians were classified as gastroenterologists, general surgeons and others. RESULTS: In 2002, 1444 physicians, including 735 surgeons, 551 gastroenterologists and 158 others, performed at least 100 colonoscopies or 100 gastroscopies. Gastroenterologists performed 53% of all colonoscopies and 59% of all gastroscopies. Gastroenterologists were the primary providers of colonoscopies in large urban areas, whereas surgeons were the primary providers in smaller urban and rural areas. An average of 317 colonoscopies were performed by surgeons, 516 by gastroenterologists and 203 by other physicians. The proportion of surgeon colonoscopists in each province ranged from 47% to 71%. CONCLUSIONS: Surgeons and gastroenterologists are the major providers of gastrointestinal endoscopy in Canada, but the distribution of these providers among provinces and urban and rural areas varies. Although surgeon endoscopists are more numerous, on average, they perform fewer procedures annually than internists.